2016
DOI: 10.1016/j.socscimed.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depressive symptoms following the Great East Japan earthquake: A prospective study

Abstract: We sought to investigate prospectively the association between exposure to disaster (the 2011 East Japan Earthquake) and change in depressive symptoms among community-dwelling older adult survivors. We used two waves of data from the Japan Gerontological Evaluation Study (JAGES), an ongoing population-based, prospective cohort study in Japan. A unique feature of our study was the availability of information about mental health status pre-dating the disaster. Our sample comprised community-dwelling survivors ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 25 publications
8
87
3
Order By: Relevance
“…Paired t-tests were used to compare GDS scores in different social ties groups. We also used a linear regression model to examine the association between the change in the neighborhood ties and the change in the GDS scores [34]. Skewness and kurtosis were calculated for the distribution of GDS scores in 2010 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Paired t-tests were used to compare GDS scores in different social ties groups. We also used a linear regression model to examine the association between the change in the neighborhood ties and the change in the GDS scores [34]. Skewness and kurtosis were calculated for the distribution of GDS scores in 2010 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…We also have reported that disruption of access to psychiatry after disasters was significantly associated with worsening of depressive symptoms. (Tsuboya et al, 2016) Disruption of access to medical service after disasters might worse not only mental function, but also physical and cognitive function for a few years among older survivors.…”
Section: Discussionmentioning
confidence: 99%
“…The study profile has been previously described in detail. (Hikichi et al, 2016; Tsuboya et al, 2016) The East Japan Earthquake and Tsunami struck on March 11th, 2011. Iwanuma city, the field site for the present study, is a coastal municipality in Miyagi prefecture in Japan, located approximately 80 km west of the epicenter of the 3.11 earthquake.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a previous study suggested that dwelling house damage caused by major disasters was associated with worsening depressive symptoms in older survivors. 13 Little evidence, however, is available for the prevention of mental health problems from a public health intervention perspective. Physical activity, which is a modifiable behaviour, has the benefit of preventing or alleviating depressive symptoms 14 15 and of treating depression 16 17 in older adults.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%